Impaired mobility and impaired working capacity among foreign born people and native born Swedes. Issue 1 (January 1998) - Pudaric, S; Sundquist, J; Johansson, S E
Abstract : OBJECTIVE: The aim of this study is to analyse the influence of country of birth and attained level of education, on impaired mobility and impaired working capacity adjusted for age, sex, and other background variables. SETTING: Sweden. DESIGN: A random sample of 5798 men and 6072 women ages 55-74 years were interviewed face to face by Statistics Sweden 1986-1993. Dependent variable: impaired mobility and impaired working capacity. Independent variables: sex, age, country of birth (Swedes, Finns, Western countries, south Europeans, and all others), attained level of education, marital status, form of tenure, and social network. This study was designed as a cross sectional study. The data were analysed with unconditional logistic regression in main effect models. The results are shown as odds ratios (OR) with 95% confidence intervals (CI). RESULTS: In general, poor health, defined as impaired working capacity or impaired mobility, proved to be more frequent among foreign born people and in all socially disadvantaged groups such as those with a low educational status, people renting a dwelling or with a poor social network. Impaired working capacity and impaired mobility were more frequent among female "all others". The impaired mobility among men and women born in south Europe was high with OR = 2.65 (CI = 1.34, 5.25) and OR = 3.17 (CI = 1.44, 7.00) in the full model. Men and women from Finland and all other countries had high risks for impaired mobility when adjusted for all background variables. Finnish men and south European women had the highest odds ratios for impaired working capacity. There was a clear gradient between educational status and impaired working capacity, with the highest odds ratios for men and women, 2.39 and 1.92, with a low attained level of education, when adjusting for the independent variables. CONCLUSION: Country of birth and educational status are two important independent factors with influence on poor health defined as impaired mobility and impaired working capacity in age 55-74.